Clique comparison and homophily detection in telecom social networks - Mandić, Marin; Škobić, Davor; Martinović, Goran (2019)
Social Network Analysis (SNA) is based on graph theory and is used for identification of the structure, behavioral patterns and social connectivity of entities. In this paper, SNA is used in the telecom industry in terms of a call detail record referring to phone call data separated into two groups, i.e., domicile network and virtual operator network data. Emphasis was placed on community detection. Comparison was made among communities detected in domicile and virtual operator networks. Results show that in contrast to domicile network, the number of cliques in the virtual operator network is larger. Also, homophily was detected between domicile network and virtual operator network users.
Bibliografija: 16 jed.
Abstract.
Keywords: Društvene mreže -- Telekomunikacije